Evaluation of Histopathological Changes of Placenta in Low Birth Weight Babies Delivered in a Tertiary Care Centre - Shah, Miki; Panta, Bibek; Shah, Bikesh; Tiwari, Archana; Shrestha, Deepak (Nepal Journal of Medical Sciences, 2025)
Introduction: Antenatal health-care given to pregnant women has great influence on the rates of perinatal morbidity and mortality. Amongst different causes of perinatal mortality, low birth weight is the single most significant factor. Therefore, routine histopathological examination of the placenta from all the low birth weight babies should be done to find out the likely cause. This study aimed to assess the pathological changes in placenta in association with low birth weight babies. Methods: A descriptive observational study was conducted from 1 April, 2022 to 31 March, 2023 in the Department of Obstetrics and Gynaecology and the Department of Pathology of Lumbini Medical College- Teaching Hospital after obtaining ethical clearance from the Institutional Review Committee (IRC-LMC-06/P-24) at Lumbini Medical College and Teaching hospital, Palpa, Nepal. A total of 83 placentas of low birth weight babies were included. The weight of the baby and placenta was taken within the first hour of birth. All the collected placentas with a portion of cord attached were sent to Department of Pathology for histopathological study and the reports were collected. All the quantitative data were expressed in frequencies and percentages. Results: The fetoplacental ratio was 5.99:1. The mean placental diameter was 14.73 centimetres while thickness was 2.95 centimetres. The umbilical cord was inserted centrally in 45, eccentric in 31, marginally in 6 cases and velamentous in 1 case. Microscopically, syncytial knot formation (75; 90.4%), perivillous fibrin deposition (49; 59%), hyalinisation (45; 54.2%), calcification (59; 71.1%), infarction (49; 59%) and hemorrhage (45; 54.2%) were found in placentas of low birth weight babies. Conclusions: Histological aberrations like presence of syncytial knots (90.4%), perivillous fibrin deposition (59%), hyalinisation (54.2%), calcification (71.1%), infarction (59%) and hemorrhage (54.2%) are observed in high rates in placentas of women with low birth weight babies.